PRASYARAT KEBERHASILAN KERJA SAMA SISTER PROVINCE : STUDI KASUS SISTER PROVINCE ANTARA JAWA TENGAH DENGAN PROVINSI FUJIAN-CINA - S., Hermini (JURNAL ILMU SOSIAL, 2014)
The implementation of Indonesian local government autonomy gives many consequences. One of it is the augmentation of cooperation with foreign countries conducted by local government. One type of the cooperation is sister province. This cooperation still bring lack of success story and best practices. Rather brings clear profits, mostly sister province cooperation has no clear benefits. By using the case of sister province cooperation between Central Java province and Fujian, this research providing the answer why central java wants to cooperate with Fujian under the scheme sister province due to the massive criticism of Free Trade Area with China. By using Scholte’s Globalization approach, and Botenbal’s lowered politics issue this paper argue that the sister province cooperation between Central Java and Fujian is being conduct for the cause of spillover effect and due to long road historical demographic background between these two provinces.